JIWA KOSMIS ST. FRANSISKUS DARI ASISI DAN KONTRIBUSINYA BAGI PENGHAYATAN SPIRITUALITAS EKOLOGI - Renwarin, Laurensius Malvin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2021)
Nowadays environmental crises are happening everywhere caused by humans who tend to try to control and exploit the environment around them. Humans regard the environment that surrounds them only as an object of need, without considering the sustainability and appreciation of the greatness of God's creation value contained in it. This kind of reality encourages people to renew their views, attitudes and behavior towards the environment. In order to renew the views, attitudes and behavior of humans, the author invites people to be friendly and love the environment through personality formation based on the cosmic spirituality of St. Francis of Assisi. In everyday life, St. Francis of Assisi was truly friendly with all of creation around him. He loves and appreciates the majesty of God which is contained in each of His creations. In the end, this friendship with creation can lead him to a harmonious relationship with God the creator. Therefore, the personality of St. Francis of Assisi needs to be imitated by humans today in order to realize the integrity of creation. Keywords: Cosmic Spirituality